"MY LAST DUCHESS": AN EXPLICATION - Gassim H. DOHAL (Association of Social and Educational Innovation, 2023)
In his poem "My Last duchess," Robert Browning uses the dramatic monologue to present the Duke to his readers. This monologue is about the Duke's last wife, addressed to the expected new duchess. Apparently, the hero of this poem is using his experience to shape his future life; this is a good way to continue the life and at the same time to avoid one's previous mistakes. Moreover, reflections on what has happened might be inspiring for an individual to model his/her future and to help others learn and manipulate their present for the sake of their future. This article will present the inspiring pictorial scene Browning has provided us with in this poem.